ANALISIS TATANIAGA JAGUNG MANIS DI KECAMATAN AMBARAWA KABUPATEN SEMARANG - Erwin Puspitasari; Bambang Sarosa (Universitas Sebelas Maret, 2003)
Sweet corn’s plants have given result for human consumption. Its produced a green corn, has delicious and sweet flavor after boiled. The sweat flavour is caused by sugar content in the send that is sukrosa 11%. As a new commodity, the market segmen of sweet corn in widely available. The aim of this research are to know the channel pattern and business institution that have a role in sweet corn’s business administration in Ambarawa of business administration economically and farmer’s share. This research used descriptive analysis method. The analysis used in this research is simple tabulation analysis method. The analysis used in this research is simple tabulation analysis based on primary data, cost analysis profit, margin, effiency of business administration and farmer’s share. And ambarawa subdistrict. Semarang regency is chosen as research location, then with largest harvest area. Jetis village is chosen. With random sampling, 30 farmer was taken as a responden. The trader sample’s taking is done with snowbill sampling by tracking back the path of sweet corn business administration from the farmer’s responden until the consument and it reached 12 responden. The taken data is primary data and secondary data. And the technic of collecting data is interview, observation and recording. The result of this research shows that there are 3 pattern of business administration’s channels. The business administration institutions are trader collector and trader retailer. Business administration cost of channel I, II, III are Rp 163, 34, Rp 30,86 and Rp 196, 58. The profit of business administration channel I, II, III are Rp 581,00, Rp 98,79 and Rp 528,62. The business administration margin chanel I, II, III Rp 730,00, Rp 129, 65, and Rp 697, 62. The efficiency of business administration economically channel I, II, III are 41,71%, 9,98% and 38, 57% farmer’s share channel I, II, III are 58, 29%, 88,21% and 60,14%.